2014
DOI: 10.1186/1471-2393-14-306
|View full text |Cite
|
Sign up to set email alerts
|

B7 costimulation and intracellular indoleamine-2,3-dioxygenase (IDO) expression in peripheral blood of healthy pregnant and non-pregnant women

Abstract: BackgroundB7 costimulatory molecules are expressed on antigen presenting cells (APCs) and are important regulators of T cell activation. We investigated the role of the B7 family of costimulatory molecules in the development of the systemic maternal immune tolerance during healthy pregnancy (HP). We also aimed to investigate the intracellular expression of indoleamine-2,3-dioxygenase (IDO) and plasma levels of tryptophane (TRP), kynurenine (KYN) and kynurenic acid (KYNA), important molecules with immunoregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Studies have shown that PD-1 + T cells seem to be increased in healthy pregnant women compared to non-pregnant women [68], while decreased PD-1 + T cells were observed in PE and GDM [69][70][71]. In our studies, we found that PD-1 + Tregs in CB, PD-1 + Tregs and GITR + Tregs in PB from PE, GDM, and PROM were lower compared to those of NP.…”
Section: Discussionsupporting
confidence: 51%
“…Studies have shown that PD-1 + T cells seem to be increased in healthy pregnant women compared to non-pregnant women [68], while decreased PD-1 + T cells were observed in PE and GDM [69][70][71]. In our studies, we found that PD-1 + Tregs in CB, PD-1 + Tregs and GITR + Tregs in PB from PE, GDM, and PROM were lower compared to those of NP.…”
Section: Discussionsupporting
confidence: 51%
“…Macrophages in term placentas strongly express the B7-H2 protein (64). The expression of ICOS, a simulator of T-cell activation, is strongly elevated in healthy pregnant women, whereas its corresponding costimulatory molecule B7-H2 is decreased on monocytes of pregnant women compared with those of non-pregnant women (69). In an allogeneic CBA female × B6 male pregnancy model, blockade of the ICOS-B7-H2 pathway results in increased fetal absorption and a decreased fetal survival rate.…”
Section: B7-h2mentioning
confidence: 99%
“…PD-L1 expression by Treg cells has been found to inhibit proliferation of CD4 + CD25 − T cells and suppress expression of the pro-inflammatory cytokines IFN-γ and TNF-α (224). PD-1 expression on T cells seem to be increased in healthy pregnancy compared to non-pregnant women (225), while reduced levels of PD-1 and PD-L1 have been suggested to promote Th17 proliferation, thus causing the Treg/Th17 imbalance observed in PE (226). Consistent with this, mice studies have shown that blocking of PD-L1 results in lower numbers of Tregs and increased Teff and Th17 populations, as well as increased fetal resorption and reduced litter size (227, 228).…”
Section: The Role Of Tregs In Reproductive Biologymentioning
confidence: 99%